A Bacteriophage-Acquired O-Antigen Polymerase (Wzyβ) from P. aeruginosa Serotype O16 Performs a Varied Mechanism Compared to Its Cognate Wzyα - Taylor, Véronique L.; Hoage, Jesse F. J.; Thrane, Sandra Wingaard; Huszczynski, Steven M.; Jelsbak, Lars; Lam, Joseph S. (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa is a Gram-negative bacterium that produces highly varied lipopolysaccharide (LPS) structures. The O antigen (O-Ag) in the LPS is synthesized through the Wzx/Wzy-dependent pathway where lipid-linked O-Ag repeats are polymerized by Wzy. Horizontal-gene transfer has been associated with O-Ag diversity. The O-Ag present on the surface of serotypes O5 and O16, differ in the intra-molecular bonds, α and β, respectively; the latter arose from the action of three genes in a seroconverting unit acquired from bacteriophage D3, including a β-polymerase (Wzyβ). To further our understanding of O-polymerases, the inner membrane (IM) topology of Wzyβ was determined using a dual phoA-lacZα reporter system wherein random 3’ gene truncations were localized to specific loci with respect to the IM by normalized reporter activities as determined through the ratio of alkaline phosphate activity to β-galactosidase activity. The topology of Wzyβ developed through this approach was shown to contain two predominant periplasmic loops, PL3 (containing an RX10G motif) and PL4 (having an O-Ag ligase superfamily motif), associated with inverting glycosyltransferase reaction. Through site-directed mutagenesis and complementation assays, residues Arg254, Arg270, Arg272 and His300 were found to be essential for Wzyβ function. Additionally, like-charge substitutions, R254K and R270K, could not complement the wzyβ knockout, highlighting the essential guanidium side group of Arg residues. The O-Ag ligase domain is conserved among heterologous Wzy proteins that produce β-linked O-Ag repeat units. Taking advantage of the recently obtained whole-genome sequence of serotype O16 a candidate promoter was identified. Wzyβ under its native promoter was integrated in the PAO1 genome, which resulted in simultaneous production of α- and β-linked O-Ag. These observations established that members of Wzy-like family consistently exhibit a dual-periplasmic loops topology, and identifies motifs that are plausible to be involved in enzymatic activities. Based on these results, the phage-derived Wzyβ utilizes a different reaction mechanism in the P. aeruginosa host to avoid self-inhibition during serotype conversion.